Integrating Madrasah Diniyah into Secondary Schools: A Case Study of Local Religious Curriculum in Indonesia - Nur Alfiyah; Akhmad Nurul Kawakib; Wahidmurni; Ahmad Sholeh (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2025)
This study aims to analyze the historical implementation of local content curriculum on religion and Diniyah education in secondary schools in Jombang and its impact on the quality of Islamic education. Using a qualitative approach and case study method, data were collected through document analysis, observation, and in-depth interviews with teachers, school principals, and community leaders. The findings show that Islamic education in Jombang has developed dynamically in response to socio-cultural changes. Integrating Diniyah Education into the school curriculum represents an adaptation to diverse local needs and the complexity of religious practices in the region. This implementation has positively impacted students' religious character, enhancing worship competencies and deepening religious understanding. The study concludes that adapting the Diniyah madrasah curriculum to local cultural contexts is an effective strategy to improve the quality of Islamic education, especially in socially and religiously plural communities. It highlights the importance of local potential in formulating responsive and contextual Islamic education policies.